Building supply chain performance through halal logistics practices and organizational capabilities - Abd Mubin, Najaa (2021)
Halal industry is expanding worldwide. Therefore, it requires strong supply chain management to enhance halal business efficiency and preserve credibility through halal logistics process. However, studies on halal logistics remain limited and isolated. Therefore, this study aims to examine factors of implementation of halal logistics practices towards supply chain performance. The criteria of halal logistics practices consist of whole logistics operations, management, risk analysis, and risk process. The firms can implement these practices by analyzing their capabilities and stakeholder influences. Besides, the knowledge management process acted as a moderator while halal logistics practices mediate the relationships between organizational capabilities and supply chain performance. Meanwhile, knowledge management process is tested as a moderator on the relationships between organizational capabilities and stakeholders' influence towards halal logistics practices. A total of 4405 questionnaires were distributed to manufacturers of halal foods, cosmetics and pharmaceutical in six states within Malaysia. At the end of data collection period, a total of 270 useful questionnaires were collected for further analysis. The IBM SPSS statistics and SmartPLS 3.0 were applied to validate the research model and test the proposed hypotheses. The result confirmed that organizational capabilities and stakeholders' influences are positively related to halal logistics practices. Meanwhile, halal logistics practices are positively related to supply chain performance. Besides that, halal logistics practices were found to mediate the relationship between organizational capabilities and supply chain performance. Finally, this study found that the knowledge management process moderates the relationship between ii organizational capabilities and stakeholders' influences towards halal logistics practices. Overall, the findings of this study provide empirical evidence and insight that firms can build supply chain performance through holistic halal logistics practices. Building strong organizational capabilities and well-managed stakeholder influence can enhance the halal logistics practices in the firm's management responsibilities, risk management analysis, risk management process, and operation. This study has provided theoretical and practical implications to the existing body of research and manufacturers in Malaysia. The industry practitioners can use the results of this study as a strategy to improve their halal logistics practices if superior supply chain performance is desired.